The role of social learning in adaptiveness: insights from water management - and Lebel, Louis; Grothmann, Torsten; Siebenhüner, Bernd (International Environmental Agreements: Politics, Law and Economics, 2010)
The article introduces the notion of adaptiveness and discusses the role of social learning in it. Adaptiveness refers to the capacity of a social actor or social–ecological system to adapt in response to, or in anticipation of, changes in the environment. We explore arguments both from a theoretical perspective and through illustrations from case studies of water management in the Alps of Europe and Mekong in southeast Asia. We propose and illustrate that social learning processes are important for building adaptiveness in several ways and at different scales. Social learning can help cope with informational uncertainty; reduce normative uncertainty; build consensus on criteria for monitoring and evaluation; empower stakeholders to take adaptive actions; reduce conflicts and identify synergies between adaptations; and improve fairness of decisions and actions. Findings in the case studies provide some support for these generalizations but often with caveats related to diversity of stakeholder interests, levels of shared understanding versus contested knowledge and scale of coordination. For this reason, we suggest that future work pays greater attention to issues of agency, knowledge and scale: What strategies have individuals and organizations pursued in successful examples of social learning? How are the boundaries and interactions between science, policy and practice managed? How does social learning occur across spatial and temporal scales?
Keywords: Adaptation; European Alps; Fairness; Mekong River; Social learning; Uncertainty; Water management